2015
DOI: 10.1108/he-02-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between students’ mental health and their perspectives of life at school

Abstract: Relationships between Australian students' mental health and their perspectives of life at school. Abstract PurposeThis paper explores relationships between students' self-reported mental health and their perspectives about life at school in metropolitan Adelaide, South Australia Design/methodology/approachThe Strengths and Difficulties Questionnaire (SDQ) and a purpose designed Living and Learning at School Questionnaire (LLSQ) were administered to 1715 early adolescents in school years 7, 8 and 9. Correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Similarly, peer problems also correlate to lower achievement (Wentzel and Caldwell, 1997 ), and Malecki and Elliot ( 2002 ) found that poor social skills indicated worse performance on achievement tests. More recently, Askell-Williams and Lawson ( 2015 ) showed that children with peer problems were more likely to have lower academic motivation as well as other school-related difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, peer problems also correlate to lower achievement (Wentzel and Caldwell, 1997 ), and Malecki and Elliot ( 2002 ) found that poor social skills indicated worse performance on achievement tests. More recently, Askell-Williams and Lawson ( 2015 ) showed that children with peer problems were more likely to have lower academic motivation as well as other school-related difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, various individual and organisational factors that influence pupils' mental health and/or their likelihood to seek help to address associated problems have been identified and analysed. However, important aspects have been largely neglected, including students' perspectives of recurrent pain in relation to school (Askell-Williams & Lawson, 2015) and their implications for school culture and pedagogic practices.…”
Section: Survey Of the Fieldmentioning
confidence: 99%
“…Researchers have noted that SS are critical interpersonal factors that influence adolescent mental health outcomes; these skills include personal resources that individual students bring with them in all social interactions (Askell-Williams & Lawson, 2015; Ross, Shochet, & Bellair, 2010). SS enable students to have positive experiences interacting with adults and peers in school settings.…”
Section: Ss and Mental Healthmentioning
confidence: 99%
“…School counselors need to consider the school contexts for understanding students’ social interactions and their individual traits (Semrud-Clikeman, 2007) because middle school students are in the process of refining their SS during this critical developmental transition period. School counselors are tasked with supporting all students in achieving equal accesses to quality learning experiences, including the opportunity to enhance and manage their social and emotional capabilities (Askell-Williams & Lawson, 2015). Therefore, examining the influences of students’ level of SS and their perceived SC together in relation to their mental health outcomes is necessary.…”
Section: Ss and Mental Healthmentioning
confidence: 99%